THE APPLICATION OF MONTE CARLO ANALYSIS TO AN INVENTORY PROBLEM. - Raun, Donald L. (The Accounting Review, 1963)
Abstract The article presents the application of the Monte Carlo method to inventory problems involving uncertainty of demand and or lead-time. A general statement defining the Monte Carlo technique would be that it is a process whereby data are generated by the use of some random number generator, such as a random number table. In essence, the Monte Carlo method consists of simulating the real world to determine some probabilistic property of a population of events by the use of random sampling applied to the various components of the events. All inventory situations have certain general characteristics, each involving some aspects of cost, service and usage. One characteristic is that as an inventory increases, the cost of storing those goods will also increase but the cost resulting from an inability to fill orders will decrease. Hence, one aspect of the inventory problem is to find an inventory level, which minimizes the sum of the expected holding and shortage costs. The objective of the article is to consider a set of decisions, which will minimize total cost and provide an acceptable level of goods to satisfy the anticipated or expected demand rate.